Hemostatic parameters in Thalassemia patients; a single institute experience - Faraj, Safa A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Changes of coagulation profile have been described in patients with B-Thalassemia major. Prolongation of prothrombin time and partial thromboplastin time and reduced levels of coagulation factors and natural anticoagulants have been variously described though the mechanisms involved in the thrombotic tendency seen in some Thalassemia patients have not been fully clarified.Objectives: To investigate changes in the coagulation profile in patients with B-Thalassemia according to the available hemostatic parameters in Thalassemia patients in Al-Karama Teaching Hospital in Wasit governorate.Methods: Hemostatic variables were studied in pre-transfusion blood samples from 50 transfusion-dependent children with Beta Thalassemia (mean age 13.2 years) and from 20 healthy controls.Results: Laboratory evaluation showed thrombocytopenia in 43.5%, prolongation of prothrombin time (PT) in 54% and prolongation of activated partial thromboplastin time (aPTT) in 56% of the patients. All measured coagulation factors level were low in activity as compared with control group. Serum ferritin had positive correlation with PTT and PT (r=0.12 and r=0.11 respectively) and significant negative correlation with platelet count (r=-0.3).Conclusions: Changes in the hemostasis in Thalassemia patients is notifiable.These laboratory finding may be subclinical, but play important role in anticipation of future hemorrhagic manifestation and thrombotic events.